Library catalogues and mediation - Lucia Sardo (Informatio)
The paper presents a reflection on the role of catalogues in contemporary reality. The analysis of catalogues as instruments of mediation between library collections and users is carried out starting from the birth of what is considered modern catalographic theory, in the mid-nineteenth century, and then focusing on the consequences of the advent of digital technology on catalogues and their role.